GENDER AND FAMILY WELFARE; ISLAMIC PERSPECTIVE ON THE TRANSFORMATION OF WOMEN’S ROLES IN THE ERA OF GLOBALIZATION - Arif Nasution, Marlian; Rahmat, Paisal; Faisal, Ahmad (Al-Mubin, 2025)
In the new trend of the transformation of women's roles from the 19th century to the present, a number of issues have emerged within religious communities, causing women to face ethical and psychological dilemmas. Therefore, this study aims to describe gender and family welfare; the Islamic perspective on the transformation of women's roles in the era of globalization. This research applies the library research method with a philosophical approach and analyzes the data using an interdisciplinary perspective. The findings of the study are as follows: First, through education and the development of communication technology, both women and men have equal opportunities to access information, which allows for equality between women and men, both inside and outside the household. Second, spiritually, socially, economically, and politically, Islam, through various verses in the Qur'an, has allowed women to become modern individuals by engaging in activities just like other human beings. Third, family empowerment can be achieved by building the principle of Tawhid; making the Qur'an the guide for family life; using the criteria of faith and piety as measures of success; fostering friendly, polite, and gentle behavior within the family; and nurturing a balance between modernity and spirituality in the family. In principle, all families desire modernization, happiness, and faith. In realizing a modern family full of happiness, a woman occupies a key position